2012
DOI: 10.1212/wnl.0b013e318250d7fd
|View full text |Cite
|
Sign up to set email alerts
|

Network correlates of disease severity in multiple system atrophy

Abstract: Objective: Multiple system atrophy (MSA), the most common of the atypical parkinsonian disorders, is characterized by the presence of an abnormal spatial covariance pattern in resting state metabolic brain images from patients with this disease. Nonetheless, the potential utility of this pattern as a MSA biomarker is contingent upon its specificity for this disorder and its relationship to clinical disability in individual patients. Methods: We used [18 F]fluorodeoxyglucose PET to study 33 patients with MSA, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 28 publications
5
37
0
Order By: Relevance
“…[34][35][36] Indeed, we found that reductions in putamen DAT binding were similar for MSA-P and LBD patients; correlations of this measure with disease duration and UPDRS motor ratings were of borderline significance in the two patient groups. That said, in keeping with findings from an earlier North American MSA cohort, 7 MSARP expression in the current MSA-P sample correlated significantly with concurrent UPDRS motor ratings. While a significant correlation (p < 0.001) was observed between putamen DAT binding and PDRP expression in LBD, an analogous dopaminergic relationship with MSARP values was not present in the MSA-P cohort.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…[34][35][36] Indeed, we found that reductions in putamen DAT binding were similar for MSA-P and LBD patients; correlations of this measure with disease duration and UPDRS motor ratings were of borderline significance in the two patient groups. That said, in keeping with findings from an earlier North American MSA cohort, 7 MSARP expression in the current MSA-P sample correlated significantly with concurrent UPDRS motor ratings. While a significant correlation (p < 0.001) was observed between putamen DAT binding and PDRP expression in LBD, an analogous dopaminergic relationship with MSARP values was not present in the MSA-P cohort.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, as previously observed, patients with LBD (PDND, PDD, and DLB) exhibited increased PDRP expression, 5,8,25,26 whereas those with MSA and PSP had characteristic elevations in the corresponding disease-related patterns. 7,10,11 In contrast to the relatively symmetrical network topographies associated with PD, MSA, and PSP, CBD is characterized by highly specific hemispheric asymmetries. 6 As previously noted, 6 hemispheric asymmetries in CBDRP expression discriminated patients with CBS from those with PSP and other forms of parkinsonism.…”
Section: Discussionmentioning
confidence: 99%
“…This accords with the low PDRP expression values seen in patients with MSA. 32 Indeed, the 3 atypical phenoconverters exhibited negative subject scores, denoting subnormal network activity, which discriminated them from the other subjects with RBD. Moreover, in agreement with the earlier onset of MSA relative to PD/DLB, 33 these individuals proved to be younger than phenoconverters to PD or DLB (baseline age 5 58.8 6 8.3 years vs 71.4 6 4.3 years).…”
Section: Logistical Regression Analysis Logistical Regression Analysismentioning
confidence: 96%
“…[MSARP] (20,21)), and PSP (progressive supranuclear palsy-related pattern [PSPRP] (20,22)) to classify a North American training cohort of 167 individuals with parkinsonism with an inconclusive clinical diagnosis. These subjects underwent metabolic brain imaging an average of 2.6 y before a final clinical diagnosis was made.…”
mentioning
confidence: 99%